Nahj al-Balagha; Herald of Health - Sayed Ziaodin Olianasab (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Imam Ali (AS) is the door to the science of Prophet Mohammad (PBUH) and the most outstanding student of his school of revelation. After the Prophet (PBUH), no one is superior to him in terms of virtuosity and perfection. The Messenger of God (Peace be upon him and his household), described him by saying, "Whatever I see, you also see, and whatever I hear, you also hear. The only difference is that you are not a prophet... For downloading the full-text of this article please click here.